AfCFTA AND NIGERIA’S DEVELOPMENT: OPPORTUNITIES AND CHALLENGES IN WEST AFRICA BORDERLANDS - Ogueri Ibekwe, Emmanuel (African Journal of Social and Behavioural Sciences, 2026)
This paper interrogates the developmental implications of the African Continental Free Trade Area (AfCFTA) for Nigeria, with particular attention to the often-overlooked West African borderlands. As the continent’s most populous country and an important regional actor, Nigeria occupies a central role in shaping AfCFTA’s outcomes. The agreement, while widely framed as a pan-African milestone for economic transformation, presents a complex terrain of opportunity and constraint for Nigeria. On one hand, it holds the promise of expanded intra-African trade, export diversification, industrial revitalization, and enhanced regional cooperation. Nigeria’s strategic sectors, including agro-processing, textiles, and digital services, could benefit from access to broader markets, increased investment, and job creation. On the other hand, this paper contends that realising these benefits remains conditional upon addressing a range of domestic and sub- regional challenges. These include infrastructural deficits, border insecurity, institutional incoherence, weak productive capacity, and entrenched corruption. The analysis foregrounds the paradoxes of trade liberalisation in Nigeria’s fragile frontier regions, where informal economies, porous borders, and overlapping regulatory regimes persist. By situating borderlands as both spaces of vulnerability and sites of economic potential, the paper highlights how exclusionary governance practices, particularly the marginalisation of women-led enterprises and small-scale traders, threaten inclusive participation in AfCFTA. Through a critical political economy lens, the study argues for a development-oriented trade governance model that foregrounds institutional reform, local capacity-building, and multi-level coordination. Special emphasis is placed on integrating informal actors and SMEs into formal value chains, strengthening sub-national engagement, and harmonising policy across borders. The paper contributes to ongoing debates on regional integration, state capacity, and the reimagining of Africa’s border economies as engines of transformative growth.